Soot optical properties determined by analyzing extinction spectra in the visible near-UV: Toward an optical speciation according to constituents and structure. (November 2016) - Bescond, A.; Yon, J.; Ouf, F.-X.; Rozé, C.; Coppalle, A.; Parent, P.; Ferry, D.; Laffon, C.
Abstract: To improve the optical diagnostics of soot particles and gain an increased comprehension of the soot formation and aging mechanisms requires a better understanding of the soot refractive index. The present study evaluated the refractive index of soot generated by a miniCAST, an ethylene diffusion flame, and a PALAS GFG by interpreting specific extinction measurements in the near-UV spectrum with the help of an improved RDG-FA theory. Soot's morphology, size distribution, and bulk densities were determined and taken into account for the inversion process. Findings indicate that absorption and scattering capacities of the considered soot were strongly dependent on the amount of organic or volatile carbons and the degree of graphitization of the carbon atoms in the primary sphere (amorphous to graphitic arrangement). The proposed speciation of particles according to these properties is based on the spectral dependence of the determined refractive index for three reference aerosols representative of organic, amorphous, and ordered soot particles. Results show that by combining the refractive indices of these three aerosols it is possible to explain the high variability of most of the optical properties of soot, paving the way for a simple optical technique that permits the speciation of soot particles. Highlights: Soot refractive index is inferred from extinction spectra in UV/visible light. Inversion is based on an improved RDG-FA theory. Soot microphysic and morphological parameters are determined and used for inversion. Optical index is connected to the degree of soot maturity and organic content. An optical method for soot speciation is proposed.